Film jako narzędzie przekazu informacji w literaturze XX wieku - Ślósarz, Anna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
The authors of this article discuss the many different ways in which writer can use the literary affordances of film. Writers present diverse approach to intersubjective codes of cinema, according to the authors, while extremes emerged in literary genres. Moreover, the author’s claim, the attitude writers take to film works and means of expression of the film can be radically different. Authorial approaches range from being fascinated with film methods of presenting reality (Tadeusz Peiper) and using them as a way to stimulate the reader’s imagination (Stephen King), to ignoring such methods, regarding them as extremely conventionalized or even trivial (Zbigniew Herbert) and therefore not worthy of interest. The 460 works of ten authors were analysed to find the contexts in which the words film and movie appear. The authors found that Tadeusz Peiper was fascinated by silent films while Zbigniew Herbert, who evaluated them from perspective of time, condemned their conventions. Making references to film assisted Andrzej Stasiuk in presenting local community, and it helped Stephen King gaining global fame. Prominent playwriters either ignored affordances of film in their literary works (e.g. Samuel Beckett and Tom Stoppard) or affordances were key in their dramas: e.g. Tennessee Williams, who used numerous cinematic references to portray his characters; intersubjective communication codes made Williams’s plays popular.